A Pilot Observational Exploratory Study of Well-Being in Hospice Interdisciplinary Team Members. (March 2022) - Schneider, Catherine; Bristol, Alycia; Ford, Ariel; Lin, Shih-Yin; Brody, Abraham A.; Stimpfel, Amy Witkoski
Introduction: Well-being and turnover intent represent key aspects to the promotion of a healthy workforce. Alarming levels of burnout and low levels of well-being have been documented in health professionals across care settings. Not only do high levels of burnout, low well-being and high turnover affect health professionals, but they are associated with poor patient care. However, limited research has investigated this topic specifically in hospice interdisciplinary team (IDT) members, nurses, chaplains, social workers. Thus, the purpose of this study was to explore hospice IDT members' well-being, and turnover intent. Methods: This observational, pilot study used quantitative surveys to examine the well-being, and turnover intention at baseline and at 3 months. Twenty-five hospice IDT members at one site participated. Results: Paired t-tests and percent change demonstrated significant decreases in compassion satisfaction (44.5 vs. 42.1, p = 0.04) and secondary traumatic stress score (18.5 vs. 13.3, p = 0.0001) and a significant increase in burnout score (17.6 vs. 20.5, p = 0.03) from baseline to follow up. Employee turnover slightly decreased from baseline to follow-up. Conclusions: In this pilot study, hospice IDT members had low levels of well-being at baseline that worsened over 3-months indicating a higher potential risk for burnout. Moreover, given the COVID-19 pandemic, this may be an ominous sign of what lies ahead for hospice providers regarding turnover, leading to significant long-term staffing problems in the field. If these results hold true in a larger sample, it could necessitate developing and testing further strategies to ensure a healthy and stable workforce.